2019
DOI: 10.1007/s12185-019-02672-4
|View full text |Cite
|
Sign up to set email alerts
|

Single cord blood transplantation in Japan; expanding the possibilities of CBT

Abstract: Cord blood (CB) has been an alternative stem cell source for patients with a wide variety of hematological diseases. Cord blood confers the advantages of rapid availability and higher tolerance to two HLA antigen mismatches compared with unrelated donors, and this has increased opportunities for patients who do not have suitable donors or require urgent transplantation. Although the higher rate of engraftment failure remains a serious concern after cord blood transplantation (CBT), the mechanisms underlying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…The introduction of CBT has expanded access to allogeneic HCT for adults who need urgent HCT worldwide, and by the end of 2016, nearly 50 000 CB units had been released by public banks for allogeneic HCT . In Japan, the cumulative number of CBT for children and adults reached 15 544 in 2017 . The strength of our study was the largest sample size of adult single‐unit CBT, which included nearly all CBT as the first allogeneic HCT for adults in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of CBT has expanded access to allogeneic HCT for adults who need urgent HCT worldwide, and by the end of 2016, nearly 50 000 CB units had been released by public banks for allogeneic HCT . In Japan, the cumulative number of CBT for children and adults reached 15 544 in 2017 . The strength of our study was the largest sample size of adult single‐unit CBT, which included nearly all CBT as the first allogeneic HCT for adults in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…13 In Japan, almost all CBTs have used the grafts from single donors, but not multiple donors, as previously described. 17 Accordingly, all the grafts of cord blood as well as those of bone marrow and peripheral blood stem cells (PBSCs) were sourced from single donors, following the Japan Cord Blood Bank Network/ Japanese Marrow Donor Program standard. 17 Most PBSCs were stored as cryopreserved products using DMSO alone or freezing medium (CP-1, Kyokuto Pharmaceutical), which contains DMSO and hydroxyethyl starch (HES).…”
Section: Hematopoietic Cell Preparation Infusion and Monitoring Of mentioning
confidence: 99%
“…Kazuhiko Ikeda , 1,2 Hitoshi Ohto, 1,2 Minami Yamada-Fujiwara, 1,3 Yoshiki Okuyama, 1,4 Shin-ichiro Fujiwara , 1,5 Kazuo Muroi, 1,6 Takehiko Mori, 7 Kinuyo Kasama, 8 Heiwa Kanamori, 1,9 Tohru Iseki, 1,10 Tokiko Nagamura-Inoue, 1,11 Kazuaki Kameda, 12 Junya Kanda, 13 Kazuhiro Nagai, 14 Nobuharu Fujii, 15 Takashi Ashida, 16 Asao Hirose, 17 Tsutomu Takahashi, 18 Keiji Minakawa, 2 and Ryuji Tanosaki 1 BACKGROUND: Hematopoietic cell infusion-related adverse events (HCI-AEs) in hematopoietic stem cell transplantations (HSCTs) have been largely attributed to toxicity of dimethyl sulfoxide (DMSO) for cryopreservation, but HSC products also contain various cells and plasma components. Our recent prospective study of 1125 HSCT recipients revealed the highest overall HCI-AE rate in bone marrow transplantation (BMT) using fresh/noncryopreserved products, although products of peripheral blood stem cell transplantation and cord blood transplantation (CBT) are generally cryopreserved with DMSO containing smaller plasma volumes.…”
mentioning
confidence: 99%
“…Cord blood would be used as an alternative when adult donor is not readily available in many transplant centers. The issue of relatively low stem cell dose for adult size recipient has been resolved by the application of double cord blood units, and has been proven success clinically (48,49). Whether cord blood can eventually substitute the need of a large registry is still debatable.…”
Section: Resultsmentioning
confidence: 99%